Murder and Mutilation in Early-Stuart England: A Case Study in Crime Reporting - MacMillan, Ken; Glass, Melissa (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
Although historians have long recognized that crime pamphlet authors were not very faithful reporters, it has been difficult for them to establish precisely how much fiction this literature contained because of the limited availability of other sources with which to compare them. Using a case study approach, this essay examines two murder pamphlets, both written in 1606, that describe the murder of a young boy, Anthony James, the mutilation of his sister, Elizabeth, and the conviction and execution of their alleged assailants, Agnes and George Dell. The presence of two pamphlets describing the same series of crimes was unusual, and, through a process of detailed comparison and critical interpretation, provides us with an opportunity to reflect further on the accuracy and purpose of crime reporting in early modern England. The two versions contain a great deal of contradictory information, were seemingly written for very different audiences, served a variety of functions for contemporary readers, and raise the question of whether the authors believed that justice was done in this case.